The cost and cost-effectiveness of an integrated wasting prevention and screening intervention package in Burkina Faso and Mali - Brander, Rebecca L.; Puett, Chloe; Becquey, Elodie; Leroy, Jef L.; Ruel, Marie T.; Sessou, Fidele Eric; Huybregts, Lieven (Elsevier, 2024)
Background Little is known about costs and cost-effectiveness of interventions that integrate wasting prevention into screening for child wasting.